URGENSI MENCIPTAKAN PEMBELAJARAN YANG BERKUALITAS BAGI SEORANG GURU - Abdul Hamid B (Elementary School Teacher Education (PGSD), STKIP PGRI Sumenep, 2020)
Learning is all efforts of teaching and learning in order to create effective and efficient teaching and learning process. Learning is a process to help students to learn well. The learning activities are expected to be a better change for students who study. These changes are related to cognitive, psychomotor, and affective aspects. The main purpose of learning is to provide opportunities for students to express their abilities so that there is a better change in themselves. There are several factors that affect learning outcomes, including (1) Student, (2) Teacher, and (3) Learning Designs. To achieve these learning objectives, it is necessary to have the skills of a teacher in designing quality learning. There are several methods that can be done by teachers to create quality learning, namely: (1) Understanding Student Characteristics, (2) Developing Learning Implementation Plans, (3) Building Student Learning Motivation, (4) Mastering Learning Materials, (5) Using Innovative Learning Media, (6) Using Innovative Learning Models, (7) Interspersing with Joke in Learning Activities, (8) Conducting feedback, and (9) Conducting Evaluations.